Arts for social change an investigation of the effectiveness of choral singing and forum theatre in fostering social change based on two case studies in Glasgow And Edinburgh - Mazzuccato, Giacomo (The University of Edinburgh, 2011)
Cultural projects have a fundamental role in social change processes. Drawing from a literature review of community arts movements and community development debates in the UK, this research examines the effectiveness of two different art forms in promoting individual and community development: choral singing and Forum Theatre. Evidence is given through the investigation of two case studies: the Gorbals Community Choir, a singing project in the Gorbals area of Glasgow and Forum Theatre, a strand of popular theatre which has been examined through the work of different organisations based in Edinburgh. Results indicate a series of personal and community outcomes produced by the two art practices, which are discussed both separately and through comparative analysis. The conclusive part of the dissertation identifies recommendations for future practice and critically examines the research methods utilised.
Keywords: arts; community development; choir; forum theatre; MSc Environment & Development